Dystocia management in a Scottish Fold cat with caesarean section and ovariohysterectomy at Winadivet clinic Malang - Intan Firdha Olien Noor Al Ichsan; Hendrawan, M. Vet., Drh. Viski Fitri; Gretania Residiwati; Galuh Chandra Agustina; Winda Syafitri (Universitas Airlangga, 2025)
The causes of dystocia can be categorized into maternal and fetal factors. Dystocia is most commonly observed in queens that are giving birth for the first time. This study aims to assess the diagnosis and management of maternal dystocia in Scottish Fold cats through caesarean section (C-section). A general examination, including palpation, revealed the presence of a fetus, followed by an ultrasound to determine the number of fetuses and their viability. A hematological examination was conducted prior to the surgical procedure to assess the presence of anemia in the patient. A C-section was performed on the ventral aspect of the abdomen, followed by ovariohysterectomy after the successful removal of two live fetuses. Postoperative care involved the administration of the antibiotic Colibact, the anti-inflammatory meloxicam, supportive therapy including Channa Lakta (lactation stimulant), Channafit (immunomodulator), and the multivitamin Pantex. The results indicated that the wound of the patient, Koko cat, had closed by the third postoperative day. It can be concluded that appropriate treatment and management contribute to a rapid recovery process.